Penerapan Chain Code Algorithm Untuk Ektraksi Fitur Objek Citra Plat Kendaraan - Irawanda Irawanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Number plate is one of the identities of a motorized vehicle. The number plate consists of letters and numbers which inform the provincial code and area code where the motorized vehicle is registered. Because the number plates are unique, they are often used for recording purposes such as in parking areas. To make it easier to record vehicle number plates, identification of vehicle number plate characters is made automatically using input in the form of a number plate image. The vehicle number plate image is used as a sample in the calculation analysis process. To facilitate the calculation process using the chain code algorithm, cutting or selecting the object image of the vehicle number plate image is carried out in order to obtain a new, selected sample image, the image with the number